The Use of Combination Therapy to Overcome Diverse Challenges in Immune Checkpoint Inhibitors Treatment - Mohammed Maeed Alqhtani; Mohammed Saad Abdullah Alqahtani; Ahmed Abdullah Alshahrani; Yasser Saad Shalan; Ali Hamad M Almegames; Naif Saad M. Alkaraan; Abdulaziz Ali Muidh Al Karan; Abdullah Bunaydir Eid Alharbi; Mohmad Saad M Al Karani; Habiba Saleh G Alenzi; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
The potential of combination strategies with ICIs is to deliver positive outcomes for solid tumors. Clinical trial data indicate that combination approaches improve response rates, duration of response, and overall survival. Despite being in the field of immune therapy for several years, ICIs can trigger mechanisms underlying resistance and diverse immune-related adverse events. This emphasizes the need for using combination therapy with cutaneous agents. A number of clinical trials have shown promising activity and tolerability for different combination strategies that include ICIs. The studies also confirm the concept that synergy exists between the actions of different treatments acting on different pathways, and this is reflected through a different spectrum of toxicities. Preclinical studies provided insights into potential rational strategies of combination therapy with ICIs. Main areas of research that have brought new insights in combined strategies included insights into the synergy of the type I interferon pathway and PD-1 inhibitors, mechanisms of resistance to ICIs, anti-tumor activities of myeloid-derived suppressor cells, and insights into how transferred immune cells work with checkpoint inhibitors. New insights into natural killer cell biology, as well as the discovery of NK cell checkpoints, expanded the portfolio of combination treatment areas. Advances in technology enabled in-depth state-of-the-art characterization and functional studies of the immune system at the single-cell level. A new era of combination therapy that is under development in several different cancers, other than hematologic malignancies, refers to the use of multiple drugs operating in the immune and non-immune pathways with anticancer agents.